Absorption versus adsorption: high-throughput computation of impurities in 2D materials - Joel Davidsson; Fabian Bertoldo; Kristian S. Thygesen; Rickard Armiento (npj 2D Materials and Applications, 2023)
Abstract Doping of a two-dimensional (2D) material by impurity atoms occurs via two distinct mechanisms: absorption of the dopants by the 2D crystal or adsorption on its surface. To distinguish the relevant mechanism, we systematically dope 53 experimentally synthesized 2D monolayers by 65 different chemical elements in both absorption and adsorption sites. The resulting 17,598 doped monolayer structures were generated using the newly developed ASE DefectBuilder—a Python tool to set up point defects in 2D and bulk materials—and subsequently relaxed by an automated high-throughput density functional theory (DFT) workflow. We find that interstitial positions are preferred for small dopants with partially filled valence electrons in host materials with large lattice parameters. In contrast, adatoms are favored for dopants with a low number of valence electrons due to lower coordination of adsorption sites compared to interstitials. The relaxed structures, characterization parameters, defect formation energies, and magnetic moments (spins) are available in an open database to help advance our understanding of defects in 2D materials.